Cognitive Behavior Change for the Improvement of Health Care, Cognitive Function and School Achievement in Helminth Infected Children - Sakti, Hastaning (Indonesian Journal of Tropical and Infectious Disease, 2010)
Overall helminth infection prevalence in Central Java in 2002 was high (20–100%). Unfortunately, the knowledge, attitude and practice (KAP) of children and their parent's about worm infection were in general very low. Objective of this study was to determine the improvement of parents' health care behavior on helminth infected children by improving their KAP, in order to decrease re-infection rate of helminth infestation and improving school achievement. Design study is quasi experiment with pre and post test control group design on community participation toward school aged children in Sragen sub-district in Central Java. A sample of one hundred and thirty one of children deriving from a systematic random sampling was used in the study and divided into 66 children for intervention population and 65 children for control population. During the study, the children in selected area were given with 400mg chewable albendazole, and after a month, their stools were examined to find out the negatives. Parent's participation was needed in improving the KAP on re-infestation that was performed by an intervention using a module. Data were analysed using chi-square test to determine therelationship between variables among groups. Stools were examined for the presence of geohelminth's egg using Kato-Katz Technique.Three subject matters (Mathematics, Indonesian Language and Natural Science) were obtained by a special tool. Digit Span, Codingand Stroop Test were used to determine the level of cognitive function. Monitoring and the ladder-snake game were use to observe the improvement of the behavior. It revealed that re-infestation of Ascaris lumbricoides, Trichuris trichhiura and Oxyuris vermicularisoccurs 2 times greater in control group, even there was no significant different. In both groups, there was no hookworm re-infestation.A good knowledge and attitude can be predicted to be a better practice to prevent the re-infestation. Oxyuris vermicularic re-infection could have adverse effect on study Achievement (Mathematics, Indonesian Language and Natural Science) and The Cognitive Function, such as memory, attention, visual-motoric co-ordination. The moshly affected cognitive function was memory-based and specifically represented the components of the working memory. From the monitoring of health care behavior, this study found that the more convinced the mothers in changing their degree of family's health were, the higher the level of children's health was.